Chapter 11: The approach to achieving glycaemic control - The Society for Endocrinology Metabolism and Diabetes of South Africa (South African Family Practice)
Type 2 diabetes is a heterogeneous disease, with the underlying mechanism ranging from predominantly insulin resistance with relative insulin deficiency, to predominantly an insulin secretory defect with lesser degrees of insulin resistance. The relative contribution of each abnormality varies between individuals, as well as within the same individual at different stages of the disease. People with type 2 diabetes are heterogeneous; diabetes is prevalent across all socio-economic strata, ethnic groups, age groups and weight categories, in individuals with highly variable nutrient intakes and levels of physical activity.1 In addition to phenotypic heterogeneity, there is genetic variability which may play a role in susceptibility, both to the disease itself or its complications.2 The response to treatment is heterogeneous; we see diversity in responses to the same treatments even in patients with near-identical phenotypes. It seems intuitive then, that a single uniform approach to management of such a heterogeneous disorder is unlikely to be successful. The optimal pharmacological approach to glucose control for any individual patient varies, which is why many international guidelines have endorsed individualised management, with no restriction on the choice of glucose lowering drug after initial metformin therapy.3–7 The concept of patient-centred care incorporates patients as partners in their healthcare. In practice, this means providing care that is “respectful of and responsive to individual patient preferences, needs and values, and ensures that patient values guide all clinical decisions”.3 These guidelines also have a broad target audience that includes health care professionals at all levels of expertise.